Нові матеріали з історії Чернігівського кафедрального Борисоглібського монастиря у другій половині XVIII ст. - Тригуб, О. (Сiверянський лiтопис, 2015)
Виявлені у Державному архіві Чернігівської області документи, що вперше запроваджуються до наукового обігу, висвітлюють різні аспекти історії Чернігівського
кафедрального Борисоглібського монастиря у другій половині XVIII ст. Выявленные в Государственном архиве Черниговской области документы, которые
впервые вводятся в научный оборот, освещают разные аспекты истории Черниговского
кафедрального Борисоглебского монастыря во второй половине XVIII в. The documents, which were discovered at the State Archives of Chernihiv Oblast and put
into scholarly circulation for the first time, cover different episodes of the history of Chernigov
Mother Monastery of SS Boris and Gleb in the second half of eighteenth century. Chronologically,
they cover period of 1770–1787. In particular, some documents reflect examples
of biographies of different people, which wanted to become a monks of Chernigov Mother
Monastery of SS Boris and Gleb, describes a complicated process substitution of managerial
positions in the monastery and provide information about stealing things from SS Boris and
Gleb Cathedral.